ANALISIS FORMALIN PADA IKAN ASIN DI BEBERAPA PASAR TRADISIONAL KOTA KENDARI - Mirna, Mirna (Jurnal Sains dan Teknologi Pangan, 2016)
This research aims to study the levels of formaldehyde in some salted fish market in Kendari. This research used descriptive method, where the research was conducted to determine the value of an independent variable, either one or more variables (independent) without comparison or connect with other variables. Descriptive method conducted there are two types of extensive qualitative and intensive quantitative survey. The results showed that the respondents require salted fish that are free of formaldehyde and screaning results showed that 7 out of 9 samples or 77.8% identified using formaline as a preservative. formalin levels obtained different, the highest formalin levels in the wet market 3 at 27 mg / g and the lowest levels in the wet market 2 is 15.8 mg / g. Based on the results of descriptive analysis showed that the levels of formalin contained within salted fish traded in traditional markets high (not secure) compared with the results of other studies and the tolerance limits are accepted by the body by IPCS. It can be harmful to the body if consumed continuously. Keywords: formalin, anchovies, permanganate, asidi alkalimetry